Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.5195/jyd.2020.996
|View full text |Cite
|
Sign up to set email alerts
|

America’s Moment: Investing in Positive Youth Development to Transform Youth and Society

Abstract: As the COVID-19 pandemic wears on, America’s youth are suffering in unprecedented ways as their journey to adulthood is interrupted by multiple societal effects. This thought leader piece explores the power of positive youth development in a time of national crisis. The paper outlines the effects of COVID‑19 on youths’ mental health, educational engagement, and workforce opportunities, all of which have been profoundly affected by the pandemic. The paper makes the case for increasing investment in positive you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…After the 2008–2009 economic recession, an intervention based on PYD principles has successfully ensured youth opportunities to be heard, empowered as change agents, and engaged in meaningful decisions (Frasquilho et al, 2018 ). During the Covid-19 pandemics, PYD approaches have been highlighted as the pathway forward, considering that these promote safe and structured contexts, developmental relationships with caring adults, skill-building opportunities, and chances for authentic leadership (Arnold, 2020 ). Concerning climate change, evidence also shows that opportunities to engage in meaningful actions may benefit well-being, as this gives the sense that something is being done (Clemens et al, 2020 ; Nielsen et al, 2021 ; Sanson and Bellemo, 2021 ; The Lancet Child and Adolescent Health, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…After the 2008–2009 economic recession, an intervention based on PYD principles has successfully ensured youth opportunities to be heard, empowered as change agents, and engaged in meaningful decisions (Frasquilho et al, 2018 ). During the Covid-19 pandemics, PYD approaches have been highlighted as the pathway forward, considering that these promote safe and structured contexts, developmental relationships with caring adults, skill-building opportunities, and chances for authentic leadership (Arnold, 2020 ). Concerning climate change, evidence also shows that opportunities to engage in meaningful actions may benefit well-being, as this gives the sense that something is being done (Clemens et al, 2020 ; Nielsen et al, 2021 ; Sanson and Bellemo, 2021 ; The Lancet Child and Adolescent Health, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Positive youth development is optimized when youth are engaged in decision-making, particularly when their ideas are considered and respected by supportive adults ( Benson et al, 2012 ; Duke, 2014 ; Zeldin et al, 2017 ). Creating opportunities for youth to develop their own voice is a long-established emphasis in youth development practice ( Arnold, 2020 ). Studies on youth voice have shown that the practice promotes a sense of agency, confidence, self-efficacy, empowerment, as well as community connections among youth ( Serido et al, 2011 ; Akiva et al, 2014 ; Krauss et al, 2014 ; Ramey et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, amid the pandemic, Arnold (2020) made an appeal for investment in positive youth development and specifically an investment in training and support of 4-H professionals as they turn to a whole-child approach. Fostering and sustaining developmental relationships with youth is a key feature of positive youth development and an aspect of youth development practice that should be emphasized right now as we face significant mental health challenges among youth and teens (Arnold & Rennekamp, 2020).…”
Section: Introductionmentioning
confidence: 99%